Long-range dihadron correlations in high multiplicity pp and PbPb with CMS - Padula, Sandra S. [UNESP] (My University, 2011)
Charged dihadron angular correlations measured using the CMS detector at the LHC for both pp collisions at 7 TeV and PbPb collisions at 2.76 TeV are presented. New results on the ridge correlation structure in high multiplicity pp collisions are shown, where the event multiplicity, transverse momentum and pseudorapidity gap dependence of the ridge effect is investigated using the full statistics data collected in 2010. Both short- A nd long-range dihadron correlations are also studied in PbPb collision at a nucleon-nucleon center-of-mass energy of 2.76 TeV. The dependence of the jet- A nd ridge-region shape and yield on transverse momentum and collision centrality is discussed.